Activity Based Costing ABC, Activity Based Management ABM y Activity Based Budgeting ABB - Marchione, Julio César
Los autores describen, analizan y ejemplifican los modelos Activity Based Costing (ABC), Activity Based Management (ABM) y Activity Based Budgeting (ABB)